A dinâmica em quatro obras de Matheus Bitondi para trompete solista: uma abordagem técnico-pedagógica - Stahl Junior, Mauro (2019)
This paper proposes a technical-pedagogic approach on the music dynamics played on the trumpet by using four pieces by the Brazilian composer Matheus Bitondi for solo trumpet in chamber music - duet setting. The research, study and practice of music expression tools can aid on the performance of a piece. The present compositions were selected through a bibliographical research finding excerpts where dynamic changes occur. Later, trumpet exercises from published trumpet methods were suggested in addition to other exercises created and adapted by the author. The discussed dynamic variations were classified and the excerpts were recorded and made available through QR code enabling the reader to listen and see the recording’s sound wave patterns. In addition to the proposals and recordings this research presents a historical content on the music dynamics for trumpet in the Portuguese language, a synthesis of the research done on the topic and provides the score for the four works by Bitondi.